Drought disaster management strategies with the SWOT analysis method - Eko Supeno, Lailan Nahar, (Opción, 2020)
This study discusses Badan Penanggulangan Bencana Daerah (BPBD) strategy in drought management in a region via a qualitative research method with a descriptive research type. Data was obtained through documentation, observation and in-depth interview. The result of the study obtained in the field showed that the BPBD Kabupaten Pasuruan strategy in drought disaster management used all of the existing strategies from the result of Strength, Weakness, Opportunity and Threat (SWOT) analysis. In conclusion, Drought disaster management carried out by BPBD based on the SWOT method results in pre-disaster, disaster responsive and post-disaster strategies.